The Core Teachings of Islam in Serat Bab Agami Yahudi, Kristen, saha Islam - Muhammad Heno Wijayanto (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This study discusses the core teachings of Islam in an ancient manuscript entitled Serat Bab Agami Yahudi, Kristen, saha Islam (SBAYKI). The manuscript which contains three texts, namely Jewish, Christian, and Islamic religion chapters, in this study is part of the text of the Islamic religion chapter. The question in this study is what is the essence of the Islamic religion contained in the SBAYKI, Islamic religion chapter?. The position of this research is to explain the main teachings of Islam contained in a manuscript, especially SBAYKI, with a philo-theological approach. A philo-theological approach is used to study manuscripts containing religious teachings accompanied by quotations from the Qur’an in them. The results of this study are the core of the teachings of Islam in the SBAYKI section of the chapter on Islamic religion, namely the etymology of Islam, the pillars of the Islamic religion (Iman, Islam, Iksan), the history and content of the Qur’an, branches of Islamic religious knowledge (Tawhid, Fiqh, Sufism), and other Islamic laws in the Qur’an